Work Safety Risk Analysis Using Hirarc Method In Iron Production Area PT. Java Rakindo - Bagas Novtantino (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2022)
HIRARC (Hazard Identification, Risk Assessment and Risk Control) is a series of processes to identify hazards that can occur in routine or non-routine activities in the company, then carry out a risk assessment of these hazards and then create a hazard control program so that the risk level can be minimized to a lower level. with the aim of preventing accidents. The implementation of K3 begins with good planning including, identification of hazards, assessment and risk control which are part of risk management. HIRARC is what determines the direction of K3 implementation in the company. This study aims to determine the risk analysis of occupational safety and health in the work production section of PT. Java Rakindo This type of research is a quantitative study using a descriptive approach. The population in this study were all workers in the work environment at PT. Java Rakindo with a total sampling technique that is as many as 25 respondents who are in the iron production section. The data were analyzed using univariate to describe the respondent's characteristics and to analyze each variable. K3 risk analysis using the HIRARC method obtained an assessment that the most dominant K3 hazard is substitution hazard of 72% (high). K3 risk assessment with a moderate level of risk category (Medium) of 84%. Administrative control of 92% and control of PPE by 100% so that it can be said that it has not been fully implemented (50%-90%).